The effect of three different sets method used in resistance training on hypertrophy and maximal strength changes - Barbaros Demirtaş; Onat Çetin; Ergün Çakır; Malik Beyleroğlu (Physical Education of Students)
Background and Study Aim. To compare the effects of three different sets method, which is frequently used in resistance training, on strength and hypertrophy values.